If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = -2 + -4x Reorder the terms: 5 + 3x = -2 + -4x Solving 5 + 3x = -2 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 5 + 3x + 4x = -2 + -4x + 4x Combine like terms: 3x + 4x = 7x 5 + 7x = -2 + -4x + 4x Combine like terms: -4x + 4x = 0 5 + 7x = -2 + 0 5 + 7x = -2 Add '-5' to each side of the equation. 5 + -5 + 7x = -2 + -5 Combine like terms: 5 + -5 = 0 0 + 7x = -2 + -5 7x = -2 + -5 Combine like terms: -2 + -5 = -7 7x = -7 Divide each side by '7'. x = -1 Simplifying x = -1
| -4.9x^2+6.88x-1.25=0 | | (3s+5)(2x-6)=0 | | 5-3w=10 | | 5(1+2n)+4= | | 6X+2=8X | | 14=v+3+6 | | 40p=60+40p | | 0.30x+.25(b)=0.60(12) | | 3x+4x+5=68 | | 22=4f-6 | | -9-2x=-5 | | -3r^2-9r=0 | | 9(u-3)=6u-48 | | v^2+10v=5 | | 4-3w=4w+w-7 | | 2x+2a=4b | | -5(7+m)=-125 | | 7-8v=3v-8 | | 4=6+x/3 | | 4+7(x-2x)=60 | | 2n-5n=-3 | | -4.9x+6.88x-1.25=0 | | -35-2r=-3r+4(2r-7) | | 21+8p=-2(4-p)-7 | | p-2/6=p-4 | | a+b-c=d | | 5h+2-(h)=22 | | 7=7-10x | | -4.9x+7.25x-1.25=0 | | 9+4y=2(3-1) | | 2.3+3n=0.8n+12 | | 2(x-4)+3x=4(x-5) |